Pendaftaran Tanah Sebagai Aset Pemerintah yang Dipergunakan untuk Sekolah (Studi Kasus MAN 2 Kota Padang Panjang) - Amelia, Allifa (Riau Law Journal, 2024)
The land for the MAN 2 School in Padang Panjang City as a Government Asset has not yet had all its land certificates registered. Based on this, the problem formulation in this thesis is How to acquire MAN 2 Padang Panjang City school land as a government asset (Ministry of Religion), How is the process of registering MAN 2 Padang Panjang City land as a government asset (Ministry of Religion). This type of research can be classified as empirical juridical research. The results of the research and discussion show that the acquisition of land for the MAN 2 Padang Panjang City School based on documentary evidence owned by Man 2 Padang Panjang City was through a Use Rights Agreement made in 1967 and some through a sale and purchase process. However, the next generation of land owners with the Right to Use did not recognize the letter so that the school could not use the letters as proof and the basis for rights and land registration originating from buying and selling did not have complete conditions so that the implementation of school land registration as a Government Aset (ministry of religion) at BPN Tanah Datar Regency.@font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-536870145 1107305727 0 0 415 0;}@font-face {font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-536859905 -1073732485 9 0 511 0;}p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:0cm; margin-bottom:8.0pt; margin-left:0cm; line-height:107%; mso-pagination:widow-orphan; font-size:12.0pt; mso-bidi-font-size:11.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-ansi-language:IN; mso-fareast-language:EN-US;}p {mso-style-priority:99; mso-margin-top-alt:auto; margin-right:0cm; mso-margin-bottom-alt:auto; margin-left:0cm; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman",serif; mso-fareast-font-family:"Times New Roman"; mso-ansi-language:IN; mso-fareast-language:IN;}.MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:11.0pt; mso-ansi-font-size:11.0pt; mso-bidi-font-size:11.0pt; font-family:"Calibri",sans-serif; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-font-kerning:0pt; mso-ligatures:none; mso-ansi-language:IN; mso-fareast-language:EN-US;}.MsoPapDefault {mso-style-type:export-only; margin-bottom:10.0pt; line-height:115%;}div.WordSection1 {page:WordSection1;}